Mechanisms of nodule-specific melanization in the hemocoel of the silkworm, Bombyx mori. (March 2016) - Shu, Min; Mang, Dingze; Fu, Gege Sun; Tanaka, Shiho; Endo, Haruka; Kikuta, Shingo; Sato, Ryoichi
Abstract: In the insect immune system, nodules are known to be a product of the cellular response against microorganisms and may be a preferential target for melanization. However, the mechanism of nodule-preferential melanization remains to be explored. In this study, we identified several mechanisms of nodule-preferential melanization by analyzing congregation and the activation of several factors involved in the prophenoloxidase (proPO)-activating system in the silkworm, Bombyx mori . Microorganism-binding assays revealed that B . mori larval plasma have an effective invading microorganism-surveillance network consisting of at least six pattern-recognition receptors (PRRs). We also found that a hemolymph serine proteinase, BmHP14, can bind to Saccharomyces cerevisiae . Pull-down assays showed that PRR C-type lectins form protein complexes with serine proteinase homologs, BmSPH1 and BmSPH2, which leads to the activated forms of BmSPH1 and BmSPH2 being gathered on microorganisms and trapped in nodules. Immunostaining analysis revealed that most factors in the proPO-activating system and some factors in the triggering system for antimicrobial peptide production exist in the granules of hemocytes which can gather in nodules. Western blot analysis showed that factors in the proPO-activating system are congregated in formed nodules by their concentration in plasma and aggregating hemocytes. Graphical abstract: Highlights: Bombyx mori have an effective microorganism-supervising network consisting of three families of PRRs. In the plasma, BmSPH1 and BmSPH2 are concentrated in nodules as a complex with B . mori C-type lectins. BmHP14 has binding properties that allow it to congregate on Saccharomyces cerevisiae cells, where it is activated. BmHPs congregate in nodules by concentrating in plasma and the aggregation of BmHP-producing hemocytes.